Analisis tingkat kerentanan seismik di Sumatera Barat berdasarkan nilai percepatan tanah maksimum dan intensitas maksimum (periode data gempa tahun 2007-2017) (Analysis of the level of seismic vulnerability in West Sumatra based on the value of maximum ground acceleration and maximum intensity (earthquake data period 2007-2017) ) - - Mandasari; - Syafriani; Rahmat Triyono; Robby Hendra (PILLAR OF PHYSICS, 2018)
A research on seismic vulnerability analysis in West Sumatera has been conducted based on maximum land acceleration and maximum intensity (Earthquake Data Period 2007-2017). This study used the empirical formulation of Mc.Guirre, Si and Midorikawa and Donovan to find the maximum ground acceleration value and the empirical formula of Murpy O’Brien was used to calculate its maximum intensity. The reference point used to calculate the maximum land acceleration value and the maximum intensity with 19 districts/cities in the region of West Sumatera. The research data used are data of earthquake recorded in BMKG Padang Panjang from February 2007 until December 2017 located in West Sumatera region with coordinated 3030’LS-0054’LU and 960BT-1020BT. Earthquake magnitude used in 5.0 SR-8.1 SR with 10-208 km depth of earthquake. Determining the seismic susceptibility level based on the calculation of maximum land acceleration and maximum intensity value using Mc.Guirre empirical formula ranges from 24.93 Gal-138.79 Gal and its maximum intensity V MMI-VI MMI. For the empirical formula of Si and Midorikawa the maximum ground acceleration value ranges from 13.50 Gal-348.31 Gal and its maximum intensity V MMI-VIII MMI. As for the empirical formula of Donovan the maximum land acceleration value is 6.04 Gal-34.47 Gal and itsmaximum intensity ranges from III MMI-V MMI. Based on the calculation of the three empirical formulation used, the level of seismic vulnerability in Sumatera region that has the highest value based on the maximum land acceleration value and maximum intensity is in the Kep. Mentawai region is at a very large risk level one.